Indications and outcomes of emergency obstetric hysterectomy; a 5-year review at the Bafoussam Regional Hospital, Cameroon - Mbakwa Rickeins Mbakwa; Nicholas Tendongfor; Yannick Lechedem Ngunyi; Ekongefeyin Sintieh Nchinda Ngek; Frank Alemkia; Thomas Obinchemti Egbe (BMC, 2021)
Abstract Background Emergency Obstetric Hysterectomy (EOH) is removal of the uterus due to life threatening conditions within the puerperium. This life saving intervention is associated with life threatening complications. In our setting, little is known on EOH. Objectives To determine the prevalence, indications and outcomes of emergency obstetric hysterectomy while comparing both postpartum hysterectomy and caesarean hysterectomy. Methods A 5-year hospital-based retrospective cohort study involving medical records of patients who underwent emergency obstetric hysterectomies between 1st January 2015 and 31st December 2019, was carried out at the Bafoussam Regional Hospital (BRH) from 1st February 2020 to 30th April 2020. Cases were classified as caesarean hysterectomy (CH) or postpartum hysterectomy (PH). Epidemiological data, indications, and complications of EOH were collected and analyzed in EPI-INFO 7.2.2.1. The chi-squared test was used to compare the two groups, and bivariate analysis was used to identify indicators of adverse outcomes of EOH. Statistical significance was set at p < 0.05. Results There were 30 cases of emergency obstetric hysterectomy (24 caesarean hysterectomies and 6 postpartum hysterectomies), giving a prevalence rate of 3.75 per 1000 deliveries. The most common indication for CH, was intractable postpartum haemorrhage and uterine rupture (33.33% each), while abnormal placentation (50%) was commonly indicated for PH. Anaemia (both groups) (p = 0.013) and sepsis (PH group only, 33.33%) (p = 0.03) were the most statistically significant complications of EOH respectively. Absence of blood transfusion prior to surgery (p = 0.013) and prolonged surgery lasting 2 or more hours (p = 0.04), were significantly associated with a negative clinical outcome. Conclusion The prevalence of EOH is high. There were no differences in the sociodemographic profile, risk factors and indications of both groups. PH group was more likely to develop sepsis as complication. Lack of blood transfusion prior to surgery and prolonged surgeries were significantly associated to complication. Meticulous care and timely recognition of negative prognostic factors of delivery as well as those of EOH will help improve maternal outcomes of pregnancy.